Coalitional Presidentialism dan Kepatuhan DPR dalam Revisi UU Pilkada Agustus 2024 - Lutfia Harizuandini; Cecep Hidayat (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This research examines how the majority coalition configuration in a multi-party presidential system facilitated the practice of autocratic legalism during the revision of the Regional Head Election Law (UU Pilkada) in the House of Representatives (DPR) in August 2024. Using a qualitative approach, using a holistic single case study method and process tracing techniques, this research explores the mechanisms of power relations between the executive and legislative branches. The results show that the consolidation of President Joko Widodo's majority coalition, which holds 91.3 percent of the DPR seats, strengthened through the use of executive toolkits in the form of personal and coercive party coalition management, and the allocation of cabinet seats intertwined with reward-punishment mechanisms, has created high ideological congruence and low governing costs. This condition transforms the DPR's function into an approving mechanism for the executive, which then becomes a precondition for the operationalization of autocratic legalism through constitutional capture with selective decision-making, fast-track legislation that addresses hundreds of issue lists in approximately seven hours without public participation, and a shift from the rule of law to rule by law using the official forum of the Legislative Body as a legal cover. However, this study also found that the executive's dominance over the legislature reached its limits when faced with massive external pressure from civil society, which ultimately canceled the ratification of the revision due to a lack of quorum at the Plenary Session.